Assessment of the spatial capacity of rural areas, as illustrated by the example of the Nowy Targ municipality - Julia Gorzelany; Paulina Figas; Magdalena Wilkosz-Mamcarczyk (Acta Scientiarum Polonorum. Formatio Circumiectus)
The accelerating development of rural areas makes it necessary to look for ways to control that development, and steer it in the right direction. The current planning and strategic instruments should be complemented with spatial capacity indicators. The aim of this article is to define these indicators, and to assess the spatial capacity of rural areas, as per the example of the Nowy Targ municipality, located in the Podhale region of Poland. The sources of information for the analyses were derived from statistical data from a period of over a dozen years, concerning the socio-economic, economic, and natural (environmental) spheres. Complementary to the research, we have conducted the analysis of the existing planning, strategic, and cartographic studies. The application thereof is to help maintain the proper quality of the rural environment, and to preserve the cultural and natural heritage, which constitutes an important element in the implementation of the sustainable development policy.